Chondrodysplasia Punctata: A Case Report of Fetal Warfarin Syndrome - Songmen, Swachchhanda; Panta, Om Biju; Paudel, Sharma; Ghimire, Ram Kumar (Journal of Nepal Health Research Council, 2017)
Chondrodysplasia punctata is abnormal calcification in the cartilage of developing bones and has been seen in association with deranged vitamin K metabolism. Warfarin, an oral anticoagulant acting on vitamin K dependent clotting factors is known to cause chondrodysplasia punctata. Despite the knowledge of the condition the management of patients with prosthetic heart valves might require use of the drug for anticoagulation. Here, we present a case of a fetal warfarin syndrome in a second born child of a 27 year lady under warfarin for prosthetic heart valve. The pregnancy was complicated by polyhydramnios in third trimester and terminated at term by normal vaginal delivery. The baby was well, except for facial dysmorphism in the form of depressed nasal bridge, narrow nares and suspected left choanal atresia. Radiograph revealed stippled ephiphysis of vertebra, femora and humera supporting diagnosis of fetal warfarin syndrome. The baby did not develop any perinatal complication and was discharged home.